Age Affects Strategic But Not Spontaneous Recall in 35- and 46-Month-old Children. Issue 4 (7th August 2020) - Sonne, Trine; Kingo, Osman S.; Berntsen, Dorthe; Krøjgaard, Peter
ABSTRACT: It is well documented that young children have difficulties with strategically remembering past events. Recent evidence on event memory in 35- and 46-month-old children suggests that strategic retrieval (yes/no questions) improves with age, whereas spontaneous retrieval is relatively unaffected by age. We here replicate and extend those findings (N = 124): First, a novel free (strategic) recall test was added to improve ecological validity. Second, the free recall procedure allowed us to make direct comparisons between spontaneous and free strategic recall relative to age. The free recall test revealed similar results in the standard yes/no questions (older children outperformed younger). The direct comparison between spontaneous and free recall revealed a reliable interaction between age and retrieval mode: While the children's age did not affect spontaneous recall, the 46-month-olds outperformed the 35-month-olds on the free recall test. The results add to the accumulating evidence that spontaneous recall of events is an early developmental achievement.